2021
DOI: 10.1097/ncc.0000000000001018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Handgrip Strength and Metabolic Syndrome Among Middle-Aged and Elderly Cancer Survivors

Abstract: Background: The number of middle-aged and elderly cancer survivors is rising.Metabolic syndrome, which has been established as an important risk factor for mortality and cardiovascular disease, has also been linked to quality of life in middle-aged and elderly cancer survivors. Recent studies documented a relationship between handgrip strength and metabolic syndrome. Objective: The aim of this study was to investigate the relationship between relative handgrip strength in middle-aged and elderly cancer survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Of the 30 studies in 19 articles, 26 ( 12 , 14 , 15 , 17 , 37 50 ) were cross-sectional studies and 4 ( 50 , 51 ) were cohort studies. A total of 24 studies in 14 articles ( 12 , 14 , 17 , 38 43 , 47 51 ) originated from Asia [7 studies in 4 articles ( 14 , 42 , 43 , 50 ) from South Korea, 12 studies in 7 articles ( 12 , 38 , 39 , 47 – 49 , 51 ) from China, 4 studies in 2 articles ( 40 , 41 ) from Japan, and 1 study ( 17 ) from Singapore], 2 studies in an article ( 15 ) from the United States, 2 studies ( 37 , 44 ) from Australia, 1 study ( 46 ) from United Kingdom, and 1 study ( 45 ) from Brazil. The total sample size was 43,396 in the 30 studies (reported in 19 articles).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 30 studies in 19 articles, 26 ( 12 , 14 , 15 , 17 , 37 50 ) were cross-sectional studies and 4 ( 50 , 51 ) were cohort studies. A total of 24 studies in 14 articles ( 12 , 14 , 17 , 38 43 , 47 51 ) originated from Asia [7 studies in 4 articles ( 14 , 42 , 43 , 50 ) from South Korea, 12 studies in 7 articles ( 12 , 38 , 39 , 47 – 49 , 51 ) from China, 4 studies in 2 articles ( 40 , 41 ) from Japan, and 1 study ( 17 ) from Singapore], 2 studies in an article ( 15 ) from the United States, 2 studies ( 37 , 44 ) from Australia, 1 study ( 46 ) from United Kingdom, and 1 study ( 45 ) from Brazil. The total sample size was 43,396 in the 30 studies (reported in 19 articles).…”
Section: Resultsmentioning
confidence: 99%
“…Jamar [3 studies ( 44 46 )], Takei [16 studies in 9 articles ( 14 , 15 , 17 , 40 , 42 , 43 , 47 , 48 , 50 )], Smedley [1 study ( 37 )], Camry [1 study ( 12 )], WCS-100 [4 studies in 2 articles ( 49 , 51 )], and hydraulic hand dynamometer [1 study ( 38 )] were used to measure HGS. There were 4 studies in 2 articles ( 39 , 41 ) that did not specify the name of the handgrip dynamometer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations